2006
DOI: 10.1590/s1415-52732006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Carotenóides como alternativa contra a hipovitaminose A

Abstract: A hipovitaminose A acarreta xeroftalmia, cegueira e morte em milhares de crianças no mundo e constitui um dos principais problemas nutricionais de populações de países em desenvolvimento, incluído o Brasil. Embora haja grande disponibilidade de frutas e verduras, fontes de carotenóides no Brasil, a hipovitaminose A constitui um grave problema de saúde pública. A falta de informação da população, no que diz respeito às fontes alimentares e aos fatores que interferem na biodisponibilidade dos carotenóides, citad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
36

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 42 publications
1
31
0
36
Order By: Relevance
“…(5,(12)(13)(14)(15)(16)(17)(18)(19) The findings of this study demonstrated that A.a. presents characteristics similar to previously reported results on studies of tucumã, even in its various derivative forms in which it was examined. (7,8,19,20) Substances, such as carotenoids and polyphenols found in the oil of tucumã, were previously evaluated by de Rosso and Mercadante, (5) and Gonçalves et al, (8) who associated these compounds with the elimination of free radicals. These affirmations are corroborated with this study, because A.a. is described as rich in carotenoids and flavonoids; both compounds are known as antioxidants in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5,(12)(13)(14)(15)(16)(17)(18)(19) The findings of this study demonstrated that A.a. presents characteristics similar to previously reported results on studies of tucumã, even in its various derivative forms in which it was examined. (7,8,19,20) Substances, such as carotenoids and polyphenols found in the oil of tucumã, were previously evaluated by de Rosso and Mercadante, (5) and Gonçalves et al, (8) who associated these compounds with the elimination of free radicals. These affirmations are corroborated with this study, because A.a. is described as rich in carotenoids and flavonoids; both compounds are known as antioxidants in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Tucumã analysis show one of the highest concentrations of pro-vitamin A, representing 52 mg/100 g of pulp, with a potential antioxidant that block the harmful effects caused by free radicals. Carotenoids are essential for cell differentiation, embryonic development, vision, as well as many other functions, including potential therapeutic benefits (5,6) According to Ambrósio et al, (2006), (7) β-carotene is a powerful antioxidant that protects against cardiovascular diseases by inhibiting the oxidative process of low-density lipoprotein (LDL). Important polyphenols, such as quercetin, are also present in tucumã, which is one of the main flavonoids present in the human diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the oils extracted from palm fruits have only been characterized spectrophotometrically for their total carotenoid content (Mambrine et al, 1997, Ferreira et al, 1999Fihlo et al, 2013), and these have been considered as potential sources of carotenoids (Manorama et al, 1991;Rodriguez-Amaya, 1996). In fact, the enrichment of foods with natural sources of β-carotene, such as these palm oils, could be an alternative solution to preventing the hypo-vitaminosis A disorder in Brazilian population (Ambrosio et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…São responsáveis pelas cores das folhas e dos frutos (Britton et al, 2004;Ambrósio et al, 2006). Cerca de 50 carotenoides possuem atividade pró-vitamina A. O betacaroteno é o que apresenta maior atividade pró-vitamínica.…”
Section: Introductionunclassified